Knowledge management as an essential path to development - ZERGUINE, ABOUD (Dirassat Journal Economic Issue, 2015)
We have become information and communication technology related to the development of communities in the present era, and is the most important means for the transfer of developing societies to societies that are more sophisticated, they contribute directly to building a new society based on knowledge and how to manage them . And it highlights the important question centered on whether the knowledge management provides the ability for developing countries to overcome the traditional stages of development, so the transition to a knowledge-based path to growth and have added value is greater . It was the aim of this paper is to highlight the role of knowledge management in advancing economic development, largely in developing economies .